PENGARUH METODE PQ4R MENGGUNAKAN MEDIA FLIPBOOK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN KELAS V SD - Sartika, Tiara; Wahyuningsih, Asih; Rochmah, Eliya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Initial observations showed that 17 of 29 students (58.6%) had not met the Learning Objectives Achievement Criteria (KKTP) due to difficulties in understanding reading texts. This condition indicates the need to improve reading comprehension. This study aimed to determine reading comprehension before and after implementing the PQ4R method using flipbook media and examine its effect. A one-group pretest-posttest design was employed with 29 fifth-grade students at SDN 1 Kasugengan Kidul. Data were collected through a reading comprehension test and observation sheets. The results showed an increase in the mean score from 65.255 in the pretest to 84.324 in the posttest. The N-Gain score of 0.5638 was classified as moderate, with an effectiveness rate of 56.3781%, categorized as fairly effective. These findings indicate that the PQ4R method using flipbook media had a positive effect on improving students’ reading comprehension.